Analysis of power system parameters for islanding detection using wavelet transform - Safdar Raza; Hanya Amjad; Muhammad Umer; Aqeel Khalid (Institute of Advanced Engineering and Science, 2020)
This paper classifies the basic power system parameters based on sensitivity and performance capability. This is the basic step in selecting the suitable parameter for intelligent islanding detection technique. The behaviour of basic power system parameters is analyzed using wavelet transform under all possible islanding and non-islanding conditions. In wavelet transform, the mother wavelet plays a significant role in the extraction of parameter features. The db4 mother wavelet is selected after an extensive analysis on different mother wavelets. As a result, it has been found that the extracted feature of reactive power shows the highest capability to distinguish islanding from non-islanding events.